Broad MICA/B expression in the small bowel mucosa: a link between cellular stress and celiac disease - Allegretti, Yessica Lorena (2013)
The MICA/B genes (MHC class I chain related genes A and B) encode for non conventional class I HLA molecules which have no role in antigen presentation. MICA/B are up-regulated by different stress conditions such as heat-shock, oxidative stress, neoplasic transformation and viral infection. Particularly, MICA/B are expressed in enterocytes where they can mediate enterocyte apoptosis when recognised by the activating NKG2D receptor present on intraepithelial lymphocytes. This mechanism was suggested to play a major pathogenic role in active celiac disease (CD). Due to the importance of MICA/B in CD pathogenesis we studied their expression in duodenal tissue from CD patients. By immunofluorescence confocal microscopy and flow cytometry we established that MICA/B was mainly intracellularly located in enterocytes. In addition, we identified MICA/B+ T cells in both the intraepithelial and lamina propria compartments. We also found MICA/B+ B cells, plasma cells and some macrophages in the lamina propria. The pattern of MICA/B staining in mucosal tissue in severe enteropathy was similar to that found in in vitro models of cellular stress. In such models, MICA/B were located in stress granules that are associated to the oxidative and ER stress response observed in active CD enteropathy. Our results suggest that expression of MICA/B in the intestinal mucosa of CD patients is linked to disregulation of mucosa homeostasis in which the stress response plays an active role.